A slurry-filled, corrosion-resistant, long-life sagger and its preparation method and application
By using the pressurized permeation and sintering technology of filler slurry, a high-life corrosion-resistant sachet was prepared, which solved the problems of short service life and unstable thermal shock in the existing sachet, and improved the mechanical strength, corrosion resistance and thermal shock stability of the sachet.
Patent Information
- Application Number
- CN202411287218.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-09-13
AI Technical Summary
The existing sash has a short service life and is easily damaged by alkaline osmotic corrosion and thermal shock during the calcination of lithium battery positive electrode materials, resulting in peeling, bulging, cracking and other phenomena.
The filling slurry is prepared with a high-life corrosion resistance slurry. The filling slurry is composed of 40%-60% solid aggregate, 25%-35% binder and dispersant. The filling slurry is filled by pressurized penetration and sintering, and a stable inorganic macromolecular structure and corrosion-proof coating are formed.
It significantly enhances the mechanical strength, corrosion resistance and thermal shock stability of the silo, reduces the thermal expansion coefficient, and extends the service life of the positive electrode material of lithium-ion battery.
Smart Images

Figure CN119100766B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of sagger preparation, and in particular to a sagger filled with slurry, corrosion-resistant and long-life sagger, and a preparation method and application thereof. Background Art
[0002] Lithium-ion battery positive electrode materials have the advantages of high energy density, long service life and stable performance. They are widely used in mobile communications, aerospace and military fields. The sagger used for calcination and synthesis of lithium battery positive electrode materials plays an important role in improving the production efficiency of lithium battery positive electrode materials, reducing production costs and improving the production environment.
[0003] At present, the service life of saggers is relatively short. During use, on the one hand, they are corroded by the alkaline penetration of the lithium battery positive electrode material. On the other hand, the temperature in the calcination process changes from low temperature to high temperature and then to rapid cooling, which is repeated over and over again, eventually leading to peeling, bulging, cracking and other phenomena.
[0004] Therefore, it is urgent to develop a sagger with strong corrosion resistance and thermal shock stability. Summary of the invention
[0005] The purpose of the present application is to provide a filling slurry, a corrosion-resistant and long-life sagger, and a preparation method and application thereof, so as to solve the above-mentioned problems.
[0006] To achieve the above objectives, the first aspect of the present application provides a filling slurry, wherein the raw materials thereof, calculated by mass ratio of 100%, include:
[0007] 40%-60% solid aggregate, 25%-35% binder, and the rest is dispersant;
[0008] The solid aggregate comprises component A and component B;
[0009] The component A includes one or more of aluminum oxide powder, magnesium oxide powder, zirconium oxide, and silicon oxide;
[0010] The component B includes one or more of calcium titanate, calcium zirconate, silicon carbide and boron carbide.
[0011] Optionally, the filling slurry satisfies at least one of the following conditions:
[0012] A. The binder includes one or more of magnesium dihydrogen phosphate, condensed aluminum phosphate, sodium silicate, and lithium silicate;
[0013] B. The dispersant includes water.
[0014] Optionally, the filling slurry satisfies at least one of the following conditions:
[0015] A. The mass ratio of the component A to the component B is (3-6): 1;
[0016] B. The particle size of component A is 1 micron to 10 microns.
[0017] A second aspect of the present application provides a corrosion-resistant and long-life sagger, the raw materials of which include the filling slurry.
[0018] The third aspect of the present application provides a method for preparing the corrosion-resistant and long-life sagger, comprising:
[0019] Adding the filling slurry into the sagger to be treated;
[0020] The filling slurry is pressurized to infiltrate the sagger, so that the sagger to be treated is partially infiltrated and filled with the filling slurry, thereby obtaining a treated sagger;
[0021] After the treatment, the sagger is sintered and cooled to obtain a corrosion-resistant and long-life sagger.
[0022] Optionally, the method for preparing the corrosion-resistant and long-life sagger meets at least one of the following conditions:
[0023] A. The ratio of the thickness of the filling slurry added to the sagger to be treated to the thickness of the sagger to be treated is (0.3-0.6):1;
[0024] B. The thickness of the remaining filling slurry in the sagger after the treatment is 1 mm to 3 mm.
[0025] Optionally, the pressure of the pressurized infiltration is 1×10 3 MPa-3×10 3 MPa, penetration time is 1h-2h, and temperature is 150℃-240℃.
[0026] Optionally, the sintering includes a first sintering and a second sintering performed sequentially;
[0027] The heating rate of the first sintering is 10°C / min-20°C / min, and the terminal temperature is 400°C-450°C;
[0028] The heating rate of the second sintering is 5°C / min-10°C / min, the holding temperature is 850°C-950°C, and the holding time is 2h-4h.
[0029] Optionally, the cooling rate is 5°C / min-10°C / min.
[0030] A fourth aspect of the present application provides an application of the corrosion-resistant and long-life sagger for preparing positive electrode materials for lithium-ion batteries.
[0031] Compared with the prior art, the beneficial effects of this application include:
[0032] The filling slurry provided in the present application, component A can react with the binder, can promote the dehydration and condensation of the binder molecules into linear molecules, and continue to transform into a network structure, and finally form a stable inorganic macromolecular structure; component B belongs to the cubic crystal system, has the characteristics of high melting point and stable crystal structure, and has high mechanical strength and small thermal expansion coefficient; through the combination of component A and component B, the mechanical strength of the sagger after filling the slurry is increased, the thermal expansion coefficient is reduced, and the corrosion resistance and thermal shock stability are enhanced.
[0033] The corrosion-resistant and long-life sagger provided by the present application has enhanced mechanical strength, corrosion resistance, and thermal shock stability, and reduced thermal expansion coefficient.
[0034] The preparation method of the corrosion-resistant and long-life sagger provided in the present application is to fill part of the filling slurry into the interior of the sagger to be treated by pressurized infiltration, and the slurry fills as many pores inside the sagger as possible through external force pressure, effectively reducing the porosity of the sagger, and preventing the penetration and erosion of the lithium battery positive electrode material to a great extent; in addition, the remaining filling slurry remains in the sagger after treatment, and after high-temperature sintering, the surface of the sagger is cured into a film to form an anti-corrosion coating under the high-temperature reaction of the binder and the aggregate, thereby achieving a secondary protection effect, and the slurry inside the sagger is also firmly bonded to the pores of the sagger due to the cross-linked network structure formed at high temperature, and is fully combined with the sagger to obtain a corrosion-resistant and long-life sagger.
[0035] The application of the corrosion-resistant and long-life sagger provided in the present application significantly enhances the average life of the corrosion-resistant and long-life sagger in the preparation of positive electrode materials for lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0037] Figure 1 This is a scanning electron microscope image of the corrosion-resistant and long-life sagger prepared in Example 1;
[0038] Figure 2 The following are comparison diagrams of the corrosion-resistant and long-life saggers prepared in Example 1 and Comparative Example 7, respectively, and the saggers after sintering 25 times. DETAILED DESCRIPTION
[0039] As used herein:
[0040] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0041] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0042] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0043] In these examples, parts and percentages are by mass unless otherwise indicated.
[0044] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0045] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0046] The first aspect of the present application provides a filling slurry, wherein the raw materials thereof, calculated by mass ratio of 100%, include:
[0047] 40%-60% solid aggregate, 25%-35% binder, and the rest is dispersant;
[0048] Optionally, the raw materials of the filling slurry are calculated based on a mass ratio of 100%, the solid aggregate can be 40%, 45%, 50%, 55%, 60% or any value between 40% and 60%, the binder can be 25%, 30%, 35% or any value between 25% and 35%, and the rest is a dispersant;
[0049] It should be noted that when the aggregate ratio is lower than 40% and the binder ratio is higher than 35%, the Baume degree of the filling slurry is too low. Through pressurized penetration, as the free water and bound water in the filling slurry evaporate, too few effective protective components remain on the surface of the sagger after treatment. The protective layer formed on the surface of the sagger after subsequent sintering is not dense enough, and the sagger surface is easily exposed, and the effect of enhancing the corrosion resistance of the sagger is not good. When the aggregate ratio is higher than 60% and the binder ratio is lower than 25%, the Baume degree of the filling slurry is too high. Through pressurized penetration, too many effective protective components remain on the surface of the sagger after treatment, the penetration force of the filling slurry is weakened, and it cannot be effectively combined with the sagger matrix, and it is easy to crack and peel during use.
[0050] The solid aggregate comprises component A and component B;
[0051] The component A includes one or more of aluminum oxide powder, magnesium oxide powder, zirconium oxide, and silicon oxide;
[0052] The component B includes one or more of calcium titanate, calcium zirconate, silicon carbide and boron carbide.
[0053] In some embodiments, the filling slurry satisfies at least one of the following conditions:
[0054] A. The binder includes one or more of magnesium dihydrogen phosphate, condensed aluminum phosphate, sodium silicate, and lithium silicate;
[0055] B. The dispersant includes water.
[0056] In some embodiments, the filling slurry satisfies at least one of the following conditions:
[0057] A. The mass ratio of the component A to the component B is (3-6): 1;
[0058] Optionally, the mass ratio of component A to component B may be 3:1, 4:1, 5:1, 6:1 or any value between (3-6):1;
[0059] It should be noted that component A has low cost and good compatibility with the binder, but its own thermal expansion coefficient is high; component B has a small thermal expansion coefficient, but high cost and poor compatibility with the binder. The protective system formed by the aggregate and binder configured in this ratio is the best.
[0060] B. The particle size of component A is 1 micron to 10 microns.
[0061] Optionally, the particle size of component A can be 1 micron, 2 microns, 3 microns, 4 microns, 5 microns, 6 microns, 7 microns, 8 microns, 9 microns, 10 microns or any value between 1 micron and 10 microns.
[0062] It should be noted that when the particle size of component A is 1 micron-10 microns, the reaction time for reacting with the binder at high temperature to generate a cross-linked network structure is reasonable, the generated protective layer has a high bonding strength with the sagger matrix, and the effect of reducing the porosity of the sagger is the best; when the particle size of component A is greater than 10 microns, the reaction time with the binder is too fast, the slurry penetration is weakened and the protective layer is unevenly cured; when the particle size of component A is less than 1 micron, the effect of reducing the porosity of the sagger is average.
[0063] A second aspect of the present application provides a corrosion-resistant and long-life sagger, the raw materials of which include the filling slurry.
[0064] The third aspect of the present application provides a method for preparing the corrosion-resistant and long-life sagger, comprising:
[0065] Adding the filling slurry into the sagger to be treated;
[0066] The filling slurry is pressurized to infiltrate the sagger, so that the sagger to be treated is partially infiltrated and filled with the filling slurry, thereby obtaining a treated sagger;
[0067] After the treatment, the sagger is sintered and cooled to obtain a corrosion-resistant and long-life sagger.
[0068] In some embodiments, the method for preparing the corrosion-resistant and long-life sagger meets at least one of the following conditions:
[0069] A. The ratio of the thickness of the filling slurry added to the sagger to be treated to the thickness of the sagger to be treated is (0.3-0.6):1;
[0070] It should be noted that when the thickness of the filling slurry added to the sagger to be treated is (0.3-0.6):1, the slurry can penetrate into the sagger to the greatest extent in the subsequent pressurized penetration, and a proper amount of slurry remains on the surface of the sagger to achieve effective protection of the sagger. When the thickness ratio is less than 0.3:1, the amount of slurry is too small, and after pressurized penetration, not enough slurry can be retained on the surface to form a protective layer on the sagger surface; when the thickness ratio is greater than 0.6:1, the amount of slurry is too much, and after pressurized penetration, too much slurry remains on the surface, which increases the manufacturing cost and causes waste.
[0071] B. The thickness of the remaining filling slurry in the sagger after the treatment is 1 mm to 3 mm.
[0072] Optionally, the thickness of the remaining filling slurry in the sagger after treatment may be 1 mm, 2 mm, 3 mm or any value between 1 mm and 3 mm.
[0073] It should be noted that when the thickness of the remaining filling slurry in the sagger after treatment is 1mm-3mm, the remaining slurry can form an effective protective layer with strong bonding force on the surface of the sagger; when the thickness of the remaining slurry is less than 1mm, the free water and bound water of the slurry evaporate after high-temperature sintering, the protective layer after curing is uneven and even the matrix is exposed, and the corrosion resistance is greatly reduced; when the thickness of the remaining slurry is greater than 3mm, the manufacturing cost increases, resulting in waste.
[0074] In some embodiments, the pressure of the pressurized infiltration is 1×10 3 MPa-3×10 3 MPa, penetration time is 1h-2h, and temperature is 150℃-240℃.
[0075] Optionally, the pressure of the pressurized infiltration can be 1×10 3 MPa, 1.5×10 3 MPa, 2×10 3 MPa, 2.5×10 3 MPa, 3×10 3 MPa or 1×10 3 MPa-3×10 3 The penetration time can be 1h, 1.5h, 2h or any value between 1h-2h, and the temperature can be 150℃, 170℃, 190℃, 200℃, 220℃, 240℃ or any value between 150℃-240℃.
[0076] It should be noted that when the pressure of pressurized penetration is 1×10 3 MPa-3×10 3MPa, the penetration time is 1h-2h, and the temperature is 150℃-240℃, all free water (source is dispersant and binder) and bound water (binder) in the filling slurry can be effectively removed, and as much filling slurry as possible can be infiltrated into the sagger matrix, which is conducive to the close combination of the sagger matrix and the filling slurry to form effective protection; when the pressure is too low and the penetration time is too short, the penetration depth is not enough, and the full combination effect of the sagger matrix and the filling slurry cannot be achieved; when the pressure is too high and the penetration time is too long, it may cause stress corrosion of the sagger and produce small cracks.
[0077] In some embodiments, the sintering includes a first sintering and a second sintering performed sequentially;
[0078] The heating rate of the first sintering is 10°C / min-20°C / min, and the terminal temperature is 400°C-450°C;
[0079] Optionally, the heating rate of the first sintering may be 10°C / min, 11°C / min, 12°C / min, 13°C / min, 14°C / min, 15°C / min, 16°C / min, 17°C / min, 18°C / min, 19°C / min, 20°C / min or any value between 10°C / min and 20°C / min, and the endpoint temperature may be 400°C, 410°C, 420°C, 430°C, 440°C, 450°C or any value between 400°C and 450°C;
[0080] It should be noted that under the conditions of the first sintering, the bond strength in the sagger was gradually improved after treatment;
[0081] The heating rate of the second sintering is 5°C / min-10°C / min, the holding temperature is 850°C-950°C, and the holding time is 2h-4h.
[0082] Optionally, the heating rate of the second sintering can be 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min, 10℃ / min or any value between 5℃ / min-10℃ / min, the holding temperature can be 850℃, 860℃, 870℃, 880℃, 890℃, 900℃, 910℃, 920℃, 930℃, 940℃, 950℃ or any value between 850℃-950℃, and the holding time can be 2h, 3h, 4h or any value between 2h-4h.
[0083] It should be noted that under the conditions of the second sintering, the effective ingredients in the binder fully react and combine with the solid aggregate, reducing the porosity of the sagger surface after treatment, and the sagger surface after treatment gradually solidifies into a film to form an anti-corrosion coating.
[0084] In some embodiments, the cooling rate is 5°C / min-10°C / min.
[0085] Optionally, the cooling rate can be 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min or any value between 5°C / min and 10°C / min.
[0086] It should be noted that a cooling rate of 5°C / min-10°C / min is helpful in preventing the sagger from cracking due to internal thermal stress.
[0087] A fourth aspect of the present application provides an application of the corrosion-resistant and long-life sagger for preparing positive electrode materials for lithium-ion batteries.
[0088] It should be noted that, on the one hand, the positive electrode material of lithium-ion batteries will generate strong alkaline substances during the calcination synthesis, and Li + Because of its small atomic number and high permeability, Li + The sagger will gradually penetrate into the internal pores of the sagger and react with the sagger to produce volume expansion. The difference in thermal expansion coefficient between the generated product and the matrix is large. Under the action of stress, the sagger will bulge, peel and crack. As a carrier for the calcined synthesis of positive electrode materials for lithium-ion batteries, the corrosion-resistant and long-life sagger provided by the present application is filled with pressurized slurry and sintered at a high temperature in the later stage to form a film on the surface of the sagger to form an anti-corrosion coating. The slurry inside the sagger is also firmly bonded to the pores of the sagger due to the cross-linked network structure formed by high temperature, and is bonded to the sagger. The full combination forms a secondary protection, which effectively reduces the porosity of the sagger, reduces the penetration and erosion of the lithium battery positive electrode material, and greatly improves the corrosion resistance of the sagger; on the other hand, during the calcination of the lithium battery positive electrode material, the temperature of the sagger increases from the initial low temperature to the high temperature, and then cools down rapidly. As the number of uses increases, the sagger is cyclically repeated, which reduces the thermal shock stability of the sagger, causes cracks and peeling, and affects the service life; the slurry provided in the present application can increase the mechanical strength of the sagger, reduce its thermal expansion coefficient, and thereby enhance the thermal shock stability of the corrosion-resistant and high-life sagger.
[0089] In some embodiments, the lithium-ion battery cathode material includes a ternary cathode material.
[0090] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0091] Example 1
[0092] In a first aspect of the present embodiment, a filling slurry is provided, wherein the raw materials thereof, calculated by mass ratio of 100%, include:
[0093] 40% solid aggregate, 30% binder, and the rest is dispersant;
[0094] The solid aggregate includes component A and component B, component A is aluminum oxide powder and magnesium oxide powder, the mass ratio of aluminum oxide powder to magnesium oxide powder is 3:1, component B is silicon carbide, and the mass ratio of component A to component B is 5:1;
[0095] The binder is lithium silicate;
[0096] The dispersant is water.
[0097] A second aspect of the present embodiment provides a method for preparing a filling slurry, wherein the above raw materials are placed in a container according to corresponding proportions and mixed evenly to obtain the filling slurry.
[0098] A third aspect of the present embodiment provides a corrosion-resistant and long-life sagger, the raw materials of which include the above-mentioned filling slurry.
[0099] A fourth aspect of the present embodiment provides a method for preparing a corrosion-resistant and long-life sagger, comprising:
[0100] The filling slurry prepared in the above process is added into the sagger to be treated, which is the sagger used for the ternary positive electrode of lithium-ion battery. The thickness ratio of the filling slurry added into the sagger to be treated is 0.5:1. The sagger is filled with temperature-controlled infiltration by a pressurized infiltration device. The pressure of the pressurized infiltration is 3×10 3 MPa, penetration time is 2 h, temperature is 150 °C;
[0101] A 3 mm thick residual filling slurry is left on the surface of the sagger after infiltration. The sagger is heated and sintered at a heating rate of 15°C / min to 420°C, then heated to 850°C at a heating rate of 5°C / min, kept warm for 2 hours, and finally cooled to room temperature at a cooling rate of 5°C / min to obtain a corrosion-resistant and long-life sagger.
[0102] The scanning electron microscope of the corrosion-resistant and long-life sagger prepared is as follows Figure 2 shown.
[0103] Example 2
[0104] In a first aspect of the present embodiment, a filling slurry is provided, wherein the raw materials thereof, calculated by mass ratio of 100%, include:
[0105] 50% solid aggregate, 25% binder, and the rest is dispersant;
[0106] The solid aggregate includes component A and component B, component A is silicon oxide, component B is calcium titanate, and the mass ratio of component A to component B is 3:1;
[0107] The binder is magnesium dihydrogen phosphate;
[0108] The dispersant is water.
[0109] A second aspect of the present embodiment provides a method for preparing a filling slurry, wherein the above raw materials are placed in a container according to corresponding proportions and mixed evenly to obtain the filling slurry.
[0110] A third aspect of the present embodiment provides a corrosion-resistant and long-life sagger, the raw materials of which include the above-mentioned filling slurry.
[0111] A fourth aspect of the present embodiment provides a method for preparing a corrosion-resistant and long-life sagger, comprising:
[0112] The filling slurry prepared in the above step was added into the sagger to be treated, which was used for the ternary positive electrode of lithium-ion battery. The thickness ratio of the filling slurry added into the sagger to be treated was 0.3:1. The sagger was filled with temperature-controlled infiltration by a pressurized infiltration device. The pressure of the pressurized infiltration was 3×10 3 MPa, penetration time is 1 h, temperature is 240 °C;
[0113] A 3 mm thick residual filling slurry is left on the surface of the sagger after infiltration. The sagger is heated and sintered at a heating rate of 20°C / min to 420°C, then heated to 850°C at a heating rate of 10°C / min, kept warm for 2 hours, and finally cooled to room temperature at a cooling rate of 5°C / min to obtain a corrosion-resistant and long-life sagger.
[0114] Example 3
[0115] In a first aspect of the present embodiment, a filling slurry is provided, wherein the raw materials thereof, calculated by mass ratio of 100%, include:
[0116] 60% solid aggregate, 25% binder, and the rest is dispersant;
[0117] The solid aggregate includes component A and component B, component A is zirconium oxide and silicon oxide, the mass ratio of zirconium oxide to silicon oxide is 1:1, component B is boron carbide, and the mass ratio of component A to component B is 4:1;
[0118] The binder is magnesium dihydrogen phosphate;
[0119] The dispersant is water.
[0120] A second aspect of the present embodiment provides a method for preparing a filling slurry, wherein the above raw materials are placed in a container according to corresponding proportions and mixed evenly to obtain the filling slurry.
[0121] A third aspect of the present embodiment provides a corrosion-resistant and long-life sagger, the raw materials of which include the above-mentioned filling slurry.
[0122] A fourth aspect of the present embodiment provides a method for preparing a corrosion-resistant and long-life sagger, comprising:
[0123] The filling slurry prepared in the above process is added into the sagger to be treated, which is the sagger used for the ternary positive electrode of lithium-ion battery. The thickness ratio of the filling slurry added into the sagger to be treated is 0.5:1. The sagger is filled with temperature-controlled infiltration by a pressurized infiltration device. The pressure of the pressurized infiltration is 2×10 3 MPa, penetration time is 2 h, temperature is 200 °C;
[0124] A 2 mm thick residual filling slurry is left on the surface of the sagger after infiltration. The sagger is heated and sintered at a heating rate of 15°C / min to 420°C, then heated to 850°C at a heating rate of 10°C / min, kept warm for 2 hours, and finally cooled to room temperature at a cooling rate of 5°C / min to obtain a corrosion-resistant and long-life sagger.
[0125] Comparative Example 1
[0126] This comparative example provides a filling slurry and a sagger and a preparation method thereof, which is different from Example 1 in that the mass ratio of the raw materials of the filling slurry in this comparative example is different from that in the example, and the raw materials are calculated by mass ratio of 100%, specifically: 30% solid aggregate, 50% binder, and the rest is dispersant; other conditions are consistent with Example 1.
[0127] Comparative Example 2
[0128] This comparative example provides a filling slurry and a sagger and a preparation method thereof, which is different from Example 1 in that the solid aggregate in the filling slurry of this comparative example is only component A, and other conditions are consistent with Example 1.
[0129] Comparative Example 3
[0130] This comparative example provides a filling slurry and a sagger and a preparation method thereof, which is different from Example 1 in that the solid aggregate in the filling slurry of this comparative example is only component B, and other conditions are consistent with Example 1.
[0131] Comparative Example 4
[0132] This comparative example provides a filling slurry and a sagger and a preparation method thereof, which is different from Example 1 in that component A in the solid aggregate of this comparative example is calcium oxide, and other conditions are consistent with Example 1.
[0133] Comparative Example 5
[0134] This comparative example provides a filling slurry and a sagger and a preparation method thereof, which is different from Example 1 in that component B in the solid aggregate of this comparative example is aluminum fluoride, and other conditions are consistent with Example 1.
[0135] Comparative Example 6
[0136] This comparative example provides a filling slurry and a sagger and a preparation method thereof, which is different from Example 1 in that: the preparation method of the sagger in this comparative example has a pressure of 4×10 3 MPa, the penetration time is 0.5 h, the temperature is 300° C., and the other conditions are consistent with those in Example 1.
[0137] Comparative Example 7
[0138] This comparative example provides a filling slurry and a sagger and a preparation method thereof, which is different from Example 1 in that: the preparation method of the sagger in this comparative example does not perform pressurized infiltration, and other conditions are consistent with Example 1.
[0139] The saggers prepared in Example 1 and Comparative Example 7 were sintered 25 times under the same sintering conditions. Figure 2 As shown (the left picture is the corrosion-resistant and long-life sagger prepared in Example 1, and the right picture is the sagger prepared in Comparative Example 7).
[0140] Comparative Example 8
[0141] This comparative example provides a filling slurry and a sagger and a preparation method thereof, which is different from Example 1 in that the preparation method of the sagger in this comparative example does not perform the first sintering, but directly performs a first sintering according to the conditions of the second sintering, and other conditions are consistent with Example 1.
[0142] Comparative Example 9
[0143] In this comparative example, the sagger described in Example 1 was used, and no treatment was performed on the sagger base. Other sintering conditions were consistent with those in Example 1.
[0144] The corrosion-resistant and long-life saggers or saggers prepared by the above embodiments and comparative examples were sintered at 850°C for 15 hours. The corrosion depth at the bottom of the sagger was observed and it was recycled until the sagger could not be used. The specific test results are shown in Table 1.
[0145] Table 1 Test results
[0146] sample Corrosion depth (mm) Sintering times Example 1 0.28 38 Example 2 0.30 37 Example 3 0.29 39 Comparative Example 1 0.36 31 Comparative Example 2 0.36 22 Comparative Example 3 0.37 20 Comparative Example 4 0.35 29 Comparative Example 5 0.39 25 Comparative Example 6 0.33 30 Comparative Example 7 0.38 25 Comparative Example 8 0.34 31 Comparative Example 9 0.40 18
[0147] From the above test results, it can be seen that according to the preferred aggregate composition, ratio, infiltration and sintering method of the present application, the number of times the lithium battery positive electrode material is sintered is 37-39 times, which is much higher than the number of times used in the comparative examples 1-9 without the experimental conditions, especially compared with the untreated sagger, the number of times the sintering is basically doubled. It shows that the experimental formula and experimental conditions used in this application are superior to others, and can greatly improve the service life of the sagger for lithium battery positive electrode materials.
[0148] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0149] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A method for preparing a corrosion-resistant and long-life sagger, characterized in that: include: Adding the filling slurry into the sagger to be treated; The filling slurry is pressurized to infiltrate the sagger, so that the sagger to be treated is partially infiltrated and filled with the filling slurry, thereby obtaining a treated sagger; The treated sagger is sintered and cooled to obtain a corrosion-resistant and long-life sagger; The raw materials of the filling slurry are calculated by mass ratio of 100%, including: 40%-60% solid aggregate, 25%-35% binder, and the rest is dispersant; The solid aggregate comprises component A and component B; The component A includes one or more of aluminum oxide powder, magnesium oxide powder, zirconium oxide, and silicon oxide; The component B includes one or more of calcium titanate, calcium zirconate, silicon carbide, and boron carbide; The binder includes one or more of magnesium dihydrogen phosphate, condensed aluminum phosphate, sodium silicate, and lithium silicate; The dispersant includes water; The mass ratio of the component A to the component B is (3-6): 1; The particle size of component A is 1 micron to 10 microns; The ratio of the thickness of the filling slurry added to the sagger to be treated to the thickness of the sagger to be treated is (0.3-0.6): 1; The thickness of the remaining filling slurry in the sagger after the treatment is 1mm-3mm; The pressure of the pressurized infiltration is 1×10 3 MPa-3×10 3 MPa, penetration time is 1h-2h, temperature is 150℃-240℃; The sintering includes a first sintering and a second sintering performed sequentially; The heating rate of the first sintering is 10°C / min-20°C / min, and the terminal temperature is 400°C-450°C; The heating rate of the second sintering is 5°C / min-10°C / min, the holding temperature is 850°C-950°C, and the holding time is 2h-4h.
2. The method for preparing the corrosion-resistant and long-life sagger according to claim 1, characterized in that: The cooling rate is 5°C / min-10°C / min.
3. A corrosion-resistant and long-life sagger, characterized in that: The sagger is prepared by the method for preparing the corrosion-resistant and long-life sagger according to claim 1 or 2.
4. An application of the corrosion-resistant and long-life sagger according to claim 3, characterized in that: Used for the preparation of positive electrode materials for lithium-ion batteries.
Citation Information
Patent Citations
Preparation method and application of high-temperature-resistant silicon carbide sagger
CN110451972A
Silicon carbide sagger for lithium battery positive electrode material and preparation method thereof
CN111170744A